Oxytocin Inhibition of Metastatic Colorectal Cancer by Suppressing the Expression of Fibroblast Activation Protein-α - Ma, Mingxing; Li, Li; Chen, He; Feng, Yong (Frontiers in Neuroscience, 2019)
Oxytocin (OXT) and its receptor (OXTR) are present in the gastrointestinal system and are involved in gastrointestinal tumorigenesis. However, the effect of OXTR signaling on the development of colorectal cancer (CRC) and its underlying mechanisms remain unexplored. To address these issues, we first examined the expressions of OXT, OXTR and several cancer-associated proteins using colon “tissue chips” from a spectrum of malignant progression of the colon, which included normal colon tissue, chronic colitis, colorectal adenoma, and colorectal adenocarcinoma (CAC). The results showed that the expressions of OXT and OXTR decreased gradually with the malignant progression of the disease. Stimulation of CAC tissues with OXT increased OXTR expression while down-regulated FAPα and CCL-2 protein expressions in a concentration- and time-dependent manner. Moreover, cell invasion experiment showed that OXT treatment reduced the invasion ability of colon cancer cells and blocking OXTR with atosiban blocked OXT-reduced invasion ability of human colon cancer cell lines Ls174T and SW480. The results indicate that OXT has the potential to inhibit CRC development via down-regulating the immunosuppressive proteins FAPα and CCL-2. When the OXTR signaling is weakened, colon tissues may transform to CRC. These findings also highlight the possibility of applying OXT to inhibit CRC development directly.